A case of broncho-cutaneous fistula secondary to tuberculosis successfully managed with awake veno-venous extracorporeal membrane oxygenation. (2021) - Correa, Genex; Taylor, Daniel; Vogel, Dominik; Wyncoll, Duncan
Abstract: A broncho-cutaneous fistula (BCF) is a communicating tract between the bronchus and the cutaneous surface of the thoracic wall and can be the primary presenting sign of several disease processes. It has been associated with positive pressure ventilation (PPV), post pneumonectomy, thoracostomy tubes, perforating chest trauma, neoplasia and chronic empyema. We report a case of a 45-year-old immunocompetent man presenting with severe hypercapnic respiratory failure secondary to a BCF as a result of tuberculosis (TB)-related empyema necessitans. Veno-venous extracorporeal membrane oxygenation (VV ECMO) was employed during spontaneous breathing to mitigate the risks of PPV, to facilitate diagnostics and enable targeted treatment. Awake VV ECMO is an effective supportive therapy for complex, destructive lung pathologies with a known reversible aetiology in which PPV would be potentially detrimental.